Fight or flight [large type] - Michaels, Fern (Thorndike Press large print dynamic drama., 2025)
"From the comfort of her beautiful mountain-top retreat, Katherine Winston creates her bestselling young adult series, Girls with Unusual Powers. No one in the nearby town has any idea of her true identity. Katherine mostly interacts with people anonymously online through fan pages. Now one of those fans appears to be in danger, and Katherine wants to help. But that means moving beyond her isolated world for the first time in years. More and more, Katherine can't shake the feeling that her fears may be justified. Someone is watching her, she's sure of it, and they're getting closer all the time. And only by leaving her self-imposed exile can she hope to find the answers she needs."--